The Relationship Between Sedentary Lifestyle And Obesity In Elementary School-Age Children At Sdn 2 Terang-Terang, Bulukumba District - Asnidar; Selfiana; Fitriani; Muriyati (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
Obesity has now become an epidemic health problem throughout the world. Its prevalence is increasing not only in Indonesia but in several other developing countries besides that, it is also increasing in several developed countries. An excessive sedentary lifestyle can cause health problems in the form of obesity. Determine the relationship between a sedentary lifestyle and the incidence of obesity in elementary school-aged children at SDN 2 Terang, Bulukumba Regency. This research is a type of analytic observational research with a cross-sectional approach, the total population is 103 students, with a total sample of 50 students consisting of class VI SD, with sampling using the probability sampling method using a sampling technique, namely random sampling. The results of this study indicate that the value of p = 0.485, so there is no significant relationship between the relationship between a sedentary lifestyle and the incidence of obesity in elementary school-age children at SDN 2 Terang-Terang, Bulukumba Regency. In this study, it can be concluded that sedentary life is high in respondents who are not obese and there is no significant relationship between sedentary lifestyle and the incidence of obesity in students of SDN 2 Terang-Terang, Bulukumba Regency, while the suggestion in this study is that elementary school-age children need awareness to better understand the things that can interfere with health problems.